Ergänzungen in den lykisch-griechischen Fragmenten TL 45 und TL 45B - Diether Schürr (Gephyra, 2021)
The beginning of the Lycian text TL 45 is restored with the usual topicalization of the direct object, but with the verb not appearing until line 3. The content of the sentence does not corre-spond to the first sentence of the Greek version. In this version, the title and the names of the archonts Hieron and Apollodotos, known from the contemporary trilingual Letöon inscrip-tion (N 320), are restored in lines 6-7. In lines 11-12 a Greek version of the Lycian theonym Trbbãmara may be restored. The Lycian text of TL 45B is revised and, as far as possible, re-stored, in comparison with N 320. The oath therein is not followed by a curse, but by a bless-ing, i. e., the rewards promised for keeping the oath. The formulation is reminiscent of a for-mulation in the Bisitun inscription of Darius I. At the end there would be room enough to restore the theonym Trbbãmara too.